E-093 Endovascular treatment of acute carotid atherosclerotic tandem occlusions: predictors of clinical outcomes as technical aspects and location of tandem occlusions. (4th August 2020) - Yoon, E; Ha, S
Abstract : Objective: We aimed to analyze angiographic and clinical outcomes according to the sequence of treatment (antegrade versus retrograde) in patients with acute ischemic stroke caused by tandem extracranial cervical carotid and intracranial large vessel occlusion. Methods: All eligible tandem occlusion patients from April 2012 to March 2019 undergoing carotid artery stenting (CAS) simultaneously with intracranial endovascular thrombectomy (EVT) were retrospectively reviewed. After dividing into 2 groups according to the treatment sequence for tandem lesions (antegrade, CAS first; retrograde, intracranial EVT first), baseline data, immediate angiographic results, and clinical outcome for eligible patients were analyzed and compared. In addition, the same analysis was performed after dividing into 3 groups based on the location of intracranial lesions (T-zone, M1, M2). Results: A total of 76 patients with a tandem occlusion (mean age, 71.7 y± 11.1) were treated with CAS and intracranial EVT. The rate of successful recanalization (TICI 2BC) was 83% (63/76), and favorable functional outcome was achieved in 49% (37/76). When comparing antegrade and retrograde methods, there were no differences in baseline data and angiographic or clinical outcomes. Favorable functional outcome was significantly higher in the M2 occlusion group ( P =0.011). In multivariate analysis, baseline NIHSS <15, age <80, and M2 occlusion were revealed as independent predictors of favorable outcome. Conclusion: Different endovascular sequences for tandem extracranial cervical carotid and intracranial large vessel occlusion do not affect angiographic or functional outcomes. Intracranial M2 occlusion, age, and baseline NIHSS were independent predictors of good clinical outcome at 3 months. Stroke; Tandem occlusion; Carotid artery stenting; Endovascular treatment; Thrombectomy Disclosures: E. Yoon: None. S. Ha: None.